Synthesis, Spectral Characterization on Few Transition Metal(II) Complexes Containing Novel Schiff Base Ligand Condensed from 3-Hydroxythiophene-2-carbaldehyde and Naphthalene-1,2-diamine (Journal of Pharmaceutical Negative Results, 2023)
Few metal complexes of Mg(II), Zn(II), Sn(II), VO(II), ions with the Schiff base ligand 2,2'-((1E,1'E)-(1,2-naphthenylenebis(azanylylidene))bis(methanylylidene))diphenol, which as prepared by the condensation of 3-hydroxythiophene-2-carbaldehyde and naphthalene-1,2- diamine, were synthesized and characterized. The solid-state isolation was used to remove the ligands and metal complexes from the reaction mixture. The UV-Visible, FT-IR and certain physio-chemical studies validated the structural and spectral features of the ligand and complexes. Studying the IR spectra of Schiff bases has shown that the N and O atoms are ligand binding sites with the metal ion. Evidence from molar conductance measurements suggests that the complexes are not electrolytic. TLC analysis was used to check the total responses. In addition to the tetrahedral geometry predicted by magnetic susceptibility data, electronic spectra for the [ZnC20H14O2N2S2], [SnC20H14O2N2S2], [VOC20H14O2N2S], [MgC20H14O2N2S] complexes indicated a square planar geometry. In order to test for antibacterial activity, the Schiff base ligands and their complexes were exposed to a disc diffusion assay.